MOLECULAR MECHANISMS OF ACTION OF MAGNESIUM OROTATE ON CARDIOVASCULAR SYSTEM - I. Yu. Torshin; O. A. Gromova (Рациональная фармакотерапия в кардиологии)
Orotic acid is one of the intermediates in the pyrimidine biosynthesis. Mechanisms of physiological effects of orotic acid are poorly known. Analysis of data about these mechanisms is presented. Effects of orotic acid and magnesium orotate on cardiovascular system as well as therapeutic implementation of magnesium orotate in cardiology are discussed.